THE EFFECTS OF RETURN ON ASSET, NET PROFIT MARGIN, AND DEBT TO: EQUITY RATIO TOWARDS PRICE TO BOOK VALUE - SULISTIANINGSIH, FITRIANI; SIAGIAN, JONNY; TOBING, EMERALD G.M. (Fundamental Management Journal, 2017)
The objective of this research is to test influence of Return on Assets (ROA), Net Profit Margin (NPM), Debt to Equity Ratio (DER) towards the Price to Book Value (PBV). The population become object in this research is service non financial sector firm listed on IDX during 2012-2015. By using purposive sampling method, the written got 15 firms to be the sample. This research used multiple linier regression analysis technique and using SPSS, in previously, the data were examined using classical assumption test.The analyze methode multiple linier regression analysis used hypothesis test, test F, and determinant coefficient. The result shows that ROA, NPM, and DER all of them have effects that significant towards price book value with 64,9% of R Square. Individually ROA, NPM, and DER have positive relation and significant toward PBV.Keywords : return on asset, net profit margin, debt to equity ratio, and price to book value